수산 음향 기법을 이용한 연안 저서 어군의 시.공간 분포 및 안정성 조사 - 강돈혁; 이창원; 조성호; 명정구; Kang, Dong-Hyug; Lee, Chang-Won; Cho, Sung-Ho; Myoung, Jung-Goo (Ocean and polar research, 2008)
Hydroacoustic technique was used to analyze spatiotemporal stability and distribution of demersal fish aggregations in the coastal region to overcome some limitations of the existing methods such as net and diving. The survey was carried out in the Baekeum Bay on the south coast of Korea in January 2007. The bottom depth in the study site ranges from 7 to 25 m. In order to outline aggregations of demersal fish initial scanning using 200 kHz split-beam transducer was randomly conducted over the large area. Having detected fish aggregation in the specific region, intensive acoustic survey of irregular star pattern was carried out along 14 transects across the area in question. The results of the acoustic survey show that all demersal fish aggregations are concentrated about 5 m from sea bottom having a slight slope and remain steady with no spatial or temporal variations during acoustic survey. The hydroacoustic method used in this study offers a new approach to understand vertical and horizontal distribution, spatiotemporal stability, and biomass estimate of demersal fish aggregations in coastal regions. Additionally, the number of individual fish estimated from in situ acoustic target strength data can be used to understand the standing stock of demersal fish aggregation.